ChemInform Abstract: Catalytic Asymmetric Synthesis of Mixed 3, 3′‐Bisindoles and Their Evaluation as Wnt Signaling Inhibitors. Issue 29 (1st July 2013) - Arai, Takayoshi; Yamamoto, Yushi; Awata, Atsuko; Kamiya, Kentaro; Ishibashi, Masami; Arai, Midori A.
Abstract: Friedel—Crafts reaction of isatin‐derived nitroalkenes with indoles in the presence of either Cu(O‐Tf)2 [conditions A)] or CuOTf [conditions B)] yields 3, 3′‐bisindoles which represent the skeleton of various indole alkaloids.